Pengaruh Store Atmosphere dan Promosi Terhadap Minat Beli di Bali Pet Nirvana Seminyak - I Made Rai Yoga Kurniawan; Ni Putu Nina Eka Lestari (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to analyze the influence of store atmosphere and promotions on consumer purchasing interest at Bali Pet Nirvana Seminyak using quantitative methods. The population of this study is social media followers and customers at Bali Pet Nirvana Seminyak, where an accidental sampling technique was used to determine the sample size of 100 people. Later, the data from the study will be analyzed with the help of SPSS (Statistical Package for the Social Science), through the stages of research instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of this study show that store atmosphere and promotions can positively and significantly influence purchasing interest at Bali Pet Nirvana Seminyak, both in partial and simultaneous forms. This indicates the importance of creating a comfortable store atmosphere and effective promotional strategies in increasing purchasing interest.